The Role of Cloudlets in Hostile Environments - Satyanarayanan, Mahadev; Lewis, Grace; Morris, Edwin; Simanta, Soumya; Boleng, Jeff; Kiryong Ha (IEEE pervasive computing, 2013)
The convergence of mobile computing and cloud computing is predicated on a reliable, high-bandwidth end-to-end network. This basic requirement is hard to guarantee in hostile environments such as military operations and disaster recovery. In this article, the authors examine how VM-based cloudlets that are located in close proximity to associated mobile devices can overcome this challenge. This article is part of a special issue on the edge of the cloud.